إستخدام كتاب "أمثلة جديدة" وتأثيره على كفاءة القواعد الصرفية لطلاب المستوى الأول في معهد الإستقامة تلاغاورو - Sudarman sudarman (LUGATUNA: Jurnal Prodi PBA, 2023)
The use of texbook can help teachers in teaching and learning arabict in particular understanding of the morphological arabic language. The use of texbook as the media intructional in the Arabic subjects expected have a positive effect in improfing student achivement, in particulary to improving the students’ ability of the morphology of Arabic language. The texbook that used in this reseach was the book of “Amtsilah Jadidah”. The purpose of this research is to determine of the effect of using book “Amtsilah Jadidah” on the ability of morphology level of the student first grade in boarding school Al Istiqamah Telagawaru West Lombok. This research used a quantitative approach with a survey from product moment corelation analysis. Based on the research result was significant effect of learning Arabic using the book “Amtsilah Jadidah” and more effective to improve students’ ability of morphology. By using the product moment corelatoin formula, the obtained value of rcount more than the value of r tabel (0,448>0,369) so that the resoult of this research is “significant” it means that alternative hypotesis (Ha) is accepted there is effect of book “Amtsilah jadidah” with the ability of morphology level of the student first grade in boarding school Al Istiqamah Telagawaru.